Active paraoxonase 1 is synthesised throughout the internal boar genital organs. Issue 3 (September 2017) - Barranco, Isabel; Perez-Patiño, Cristina; Tvarijonaviciute, Asta; Parrilla, Inmaculada; Vicente-Carrillo, Alejandro; Alvarez-Rodriguez, Manuel; Ceron, Jose J; Martinez, Emilio A; Rodriguez-Martinez, Heriberto; Roca, Jordi
Abstract : The paraoxonase type 1 (PON1) is an enzyme with antioxidant properties recently identified in the seminal plasma (SP) of several species, including the porcine. The aims of the present study were to (1) describe the immunohistochemical localisation of PON1 in the genital organs of fertile boars and (2) evaluate the relationship among PON1 activity and high-density lipoprotein cholesterol (HDL-C) concentration in fluids of the boar genital organs. Immunohistochemical analysis demonstrated that PON1 was present in testis (specifically in Leydig cells, blood vessels, spermatogonia and elongated spermatids), epididymis (specifically in the cytoplasm of the principal epithelial cells, luminal secretion and in the surrounding smooth muscle) and the lining epithelia of the accessory sexual glands (cytoplasmic location in the prostate and membranous in the seminal vesicle and bulbourethral glands). The Western blotting analysis confirmed the presence of PON1 in all boar genital organs, showing in all of them a band of 51 kDa and an extra band of 45 kDa only in seminal vesicles. PON1 showed higher activity levels in epididymal fluid than those in SP of the entire ejaculate or of specific ejaculate portions. A highly positive relationship between PON1 activity and HDL-C concentration was found in all genital fluids. In sum, all boar genital organs contributing to sperm-accompanying fluid/s were able to express PON1, whose activity in these genital fluids is highly dependent on the variable HDL-C concentration present.